Evaluation of switching treatment from high dose of darbepoetin to lower dose of roxadustat in Japanese hemodialysis patients. Issue 2 (3rd August 2021) - Kanda, Reo; Kubo, Ayano; Seki, Takuto; Urita, Atsuko; Sekiuchi, Makiho; Tomino, Yasuhiko
Abstract: Roxadustat is one of the oral hypoxia‐inducible factor prolyl hydroxylase inhibitors (HIF‐PHIs) that stimulates erythropoiesis and regulates the genes related to iron metabolism. The treatment of HIF‐PHIs is useful compared with that of erythropoietin stimulating agent (ESA) using various instruments and procedures. Few clinical researchers have examined the efficacy and safety of switching treatment from Darbepoetin to Roxadustat in Japanese hemodialysis (HD) patients. However, HIF‐PHIs have severe adverse drug reactions, such as thrombotic events. In the present study, we evaluated the lower dose of roxadustat in HD patients receiving high dose of ESA therapy. Eighteen anemic HD patients receiving an ESA, that is, , darbepoetin over 40 μg per week, were enrolled in this study. The treatment of these patients was changed to 20 mg of roxadustat three times weekly for 6 months, after which doses were adjusted to achieve a hemoglobin (Hb) target of 10.0–12.0 g/dL. An increase of 58.1 ± 32.5 mg roxadustat three times weekly increased Hb. It also achieved and then maintained levels within the target range at month 6. Ferritin levels of more than 100 ng/mL or TSAT levels of more than 20% were maintained during the 6‐month treatment periods with oral or intravenous iron supplementation. It seems unnecessary to increase the initial dose of roxadustat for patients using high doses of ESA. It is suggested that a reconsideration of the starting dose of roxadustat in Japanese HD patients is needed. (Ikegami General Hospital, Medical Corporation SHOWAKAI、Approval number: 2020–4).